A Testimony of Oenopides in Pliny - Bodnár, István (Hyperboreus, 2015)
Oenopides of Chius features in the list of foreign authorities for Book XVIII of Pliny’s Natural History. The paper assesses what this could indicate on the part of Pliny, and his source or sources, and concludes that the most likely presupposition is that some source of Pliny ascribed some speciﬁc detail about some rising and setting phenomena to Oenopides.